Quality-Oriented Islamic Education Management: Implementation of Total Quality Management in Islamic Educational Institutions - Dwi Noviatul Zahra (JISEI: Journal of Islamic Studies and Educational Innovation, 2025)
Quality-oriented management has become a strategic necessity for Islamic educational institutions in responding to the challenges of globalization, competition, and increasing stakeholder expectations. This article aims to analyze the implementation of Total Quality Management (TQM) in Islamic educational institutions as a systematic approach to improving institutional quality in an integrated and sustainable manner. Using a qualitative literature-based research method, this study examines core TQM principles such as customer satisfaction, continuous improvement, leadership commitment, teamwork, and data-based decision-making and their relevance within the values and philosophy of Islamic education. The findings indicate that the successful implementation of TQM in Islamic educational institutions requires strong leadership grounded in Islamic values, participatory management, quality-oriented organizational culture, and continuous evaluation of academic and non-academic services. Furthermore, the integration of TQM principles with Islamic educational values contributes not only to institutional effectiveness and efficiency but also to the holistic development of learners in spiritual, moral, intellectual, and social dimensions. This study concludes that TQM serves as an effective management framework for strengthening the competitiveness and sustainability of Islamic educational institutions while maintaining their distinctive religious identity.